Decoding Inclusive Beauty: Audience Reception to Beauty Standards and Disability in Digital Media Advertisements - Fithria, Khoirunnisa Nur; Sarwono, Billy K (Universitas Ahmad Dahlan, 2025)
This study explores how Indonesian audiences interpret beauty standards in digital advertisements featuring models with disabilities and examines how digital media shapes perceptions of beauty and diversity. Drawing on a qualitative approach grounded in a constructivist paradigm, this research applies Stuart Hall’s reception theory and Roland Barthes’s semiotics to analyze two popular beauty advertisements: Pond’s #WajahmuKekuatanmu (2022) and Wardah #BeautyMovesYou (2021). Data were collected through in-depth interviews with eight informants aged 18–25. Findings indicate that although both advertisements incorporate models with disabilities, their messages are interpreted differently. Pond’s ad was perceived as reinforcing conventional beauty myths, focusing on flawless skin and idealized aesthetics, whereas Wardah’s ad was more positively received for promoting empowerment and inclusion, though still subject to critique for retaining elements of perfection. Audience responses were categorized into dominant, negotiated, and oppositional readings, revealing a critical engagement with how disability and beauty are portrayed. The study highlights a gendered dimension in audience interpretation, with female informants generally more receptive to inclusive messages. It recommends that advertisers ensure authenticity by involving disability communities in production processes to avoid tokenism and misrepresentation. This research contributes to digital media and disability studies by underlining the need for deeper shifts in narrative, substance, and visual representation to achieve meaningful inclusion.